Exploration of Wettability and Optical Aspects of ZnO Nano Thin Films Synthesized by Radio Frequency Magnetron Sputtering - Kartik H. Patel; Sushant K. Rawal (Nanomaterials and Nanotechnology, 2016)
This paper aims to explore structural, optical and wettabil‐ ity aspects of zinc oxide (ZnO) nano thin films prepared by radio frequency (RF) magnetron sputtering. The deposition time is varied from 10 to 50 minutes and sputtering pressure from 0.5 to 8.0 Pa. The increase of deposition time from 10 to 50 minutes leads to formation of a single (002) peak for ZnO films; (100), (101) and (110) peaks are not observed under these conditions. The intensity for (100), (002), (101) and (110) peaks decreases with a sputtering pressure value of 3.5 Pa and above. The optical transmis‐ sion and band gaps are measured by a UV-Vis-NIR spectrophotometer. The wettability and contact-angle hysteresis (CAH) for deposited ZnO nano thin films are investigated for water, ethylene glycol, sunflower oil and formamide using a contact-angle goniometer.